Social Capital, Mental Health and Wellbeing in the Migrant Population: A Meta-Analysis - Galicia-Hernández, Tania-Evher (2025)
The following meta-analytic review focuses on the relationship between social capital and mental health in the migrant population. Based on 15 studies, with 23 samples and N = 24,000 subjects, a random effect of r = .188 (CI = .121 to .254) was found, explaining 3.5% of variance on wellbeing in comparison to 1% explained by biculturalism as strategy of acculturation. The impact of social capital is greatest on psychological well-being, medium on mental health, and least on subjective well-being. The impact of subjective cognitive measurements is greater than that of structural and mesosocial measures. The effect is greater in men, in older immigrants and in employees. The results confirm that the social capital seems to play a protective role in migrant populations’ mental health and well-being.